If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(n-4)=4(n-2)
We move all terms to the left:
2(n-4)-(4(n-2))=0
We multiply parentheses
2n-(4(n-2))-8=0
We calculate terms in parentheses: -(4(n-2)), so:We get rid of parentheses
4(n-2)
We multiply parentheses
4n-8
Back to the equation:
-(4n-8)
2n-4n+8-8=0
We add all the numbers together, and all the variables
-2n=0
n=0/-2
n=0
| 2/5n+6=2 | | 3n+13=40 | | 3x^2+31+36=0 | | -5y+7=42 | | 5.4x+35=6.9x+20 | | -5(x-11)=-75 | | 9x^2-x+4=0 | | y+3(-2)=10 | | 2x-5(x-5)=-2+4x-29 | | 12−5/1r=2r+1 | | -4(6x+1)=-24x+4 | | 26=w-14 | | 2x-5x-15=2+5x-31 | | (x+8)+(3x+24)=90 | | 8/16t=-8 | | 4+x/3+10=-1 | | x+6+33÷2=7x | | x+6+33÷2=0 | | -16x^2+96x+3=0 | | g=-6/66 | | 361=1/2xx19 | | 2c(c-3)=11(4) | | 7x-3=4x-18 | | 16x+14/3-15x=1/6 | | x+1=18-2x | | -7x-7=-43-x | | 4+6(w+2)+w=0 | | x^2-(x+1)^2=25 | | 4+6w+12=6w | | 7x+6=-x+30 | | 1/2(4a+8)=-2a+4 | | 3+6(x-2)=45 |